Development, characterization and optimization of solid lipid nanoparticles of alpha-mangostin by central composite design approach - Vutti Nagendra Babu, Gudhanti S. N. Koteswara Rao, Roja Rani Budha,, Rajasekhar Reddy Alavala, Prasanna Kumar Desu, Govada Kishore Babu, Arja Durga Prasad (Journal of Applied Pharmaceutical Science, 2023)
The study aims to formulate solid lipid nanoparticles (SLNPs) of the poorly bioavailable drug α-mangostin by central composite design and evaluate their in-vitro drug characteristics. The contribution of ingredients to the physicochemical characteristics of formulated SLNPs was investigated and further utilized to optimize the final formulation. For the formulation of SLNPs, hot melt homogenization method was used followed by a ultrasonication approach. The solid lipids used in the formulation include stearic acid and Precirol ATO5; the surfactant was Poloxamer 407, and the co-surfactant was sodium taurocholate to provide the negative charge. The optimized formulation’s mean particle size, entrapment efficiency, zeta potential, and drug loading were 173.6 nm, 72.42%, −43.3 mV, and 20.46%, respectively. X-ray diffractometry confirms the amorphous nature of SLNPs. Scanning electron microscopy analysis showed spherical morphology and a particle size range between 145 and 218 nm. Differential scanning calorimetry and Fourier transform infrared studies confirmed the absence of drug-excipient interactions. According to the findings, the optimum surfactant and lipid combination produced high-quality SLNPs with stable release properties for at least 6 months at room and refrigerator temperatures. The obtained results encourage that SLNPs can be used as oral drug delivery carriers for α-Mangostin, because of their exceptional properties.
Keywords: Central composite design, solid lipid nanoparticles, Þ-mangostin, hot melt homogenizati